Afrika Zamani: n°24, 2016 - Full Issue - Journal System (Afrika Zamani, 2021)
Contents Itinéraires et terroirs du Sahel: La poussée méridionale de longue durée dans le peuplement de l 'Afrique de l'Ouest Mamadou Fall ................................................................................. 1 Patterns of Migration and Population Mobility in Sudanic West Africa: Evidence from Ancient Kano, c. 800–1800 AD Akachi Odoemene .......................................................................... 11 Religion, Economy and the Pre-colonial Dimensions of the Jos Conflict Jacinta Chiamaka Nwaka .............................................................. 31 La politique rizicole de l’administration coloniale en Côte d’Ivoire (1898–1959) Gouédan Richard Meignan & Goly Tschiwily Bérenger ............... 45 Transformations in Beliefs and Practices of Ecological Inviolability: Historical and Contemporary Perspectives on Mamfe-Akuapem Sacred Forest in Ghana Kwabena Akurang-Parry ............................................................... 65 La revue Afrika Zamani et la vulgarisation de l’histoire africaine (1972–2001) Eugène Désiré Elounou & Jonasse Roland Nkada Mvondo ......... 91 From the Hub of Lagos: Horizontal Integration for the Southwest Region of Nigeria, a Development Imperative Kenneth Chukwuemeka Nwoko & Omon Merry Osiki ............... 111 La politique de la culture de maïs et de riz en campagne sèche : atouts et achoppements au Burkina Faso (2001–2016) Zara Dao ...................................................................................... 129